마그네트론 스퍼터링법으로 제조된 ZTZ 박막의 구조적 전기광학적 특성에 미치는 전자빔 조사의 영향 - 차병철(Byung-Chul Cha); 장진규(Jin-Kyu Jang); 최진영(Jin-Young Choi); 이인식(In-Sik Lee); 김대욱(Dae-Wook Kim); 김유성(Yu-Sung Kim); 김대일(Daeil Kim) (Biuletyn Uniejowski, 2022)
Transparent ZnO/Ti/ZnO (ZTZ) tri-layered films were prepared with radio frequency (RF) and direct current (DC) magnetron sputtering on the glass substrate. The thickness of the ZnO and Ti films was kept at 50 and 10 nm to consider the effect of the electron irradiation on the crystallization and optoelectrical properties of the films. From the XRD spectra, post-depostion electron irradiated films showed the characteristic peaks of ZnO(002) and Ti(200), respectively. the observed grain size of the ZnO(002) and Ti(200) enlarged up to 18.27 and 12.16 nm at an irradiation condition of 750 eV. In the figure of merit which means an optoelectrical performance of the films, as deposited films show a figure of merit of 2.0×10-5 -1, while the films electron irradiated at 750 eV show a higher figure of merit of 5.7×10-5 -1.